Regional Integration in the Horn of Africa: Some Findings - Yitay, Binyam; Tsoaledi Thobejane (European Journal of Social Science Education and Research, 2018)
In the Horn of Africa there is a regional bloc that comprises eight countries namely Djibouti, Eritrea, Ethiopia, Kenya, Somalia, Sudan, South Sudan and Uganda. The appellation of the organisation is called IGAD (Intergovernmental Authority on Development). It was established in 1986, yet it could not bring a desired result. Even the least form of integration i.e. Free Trade Area (FTA) could not achieve. So that this paper will probe the challenges associated with the regional integration agenda of IGAD. This paper is an excerpt from a study conducted by the author regarding IGAD. Thus the paper will present the findings of the said study. The study used qualitative approach for data collection. Interview with IGAD officers has been conducted to know the cause for the failure of IGAD’s integration process. IGAD lacks both financial and human capacity to fulfil its objectives, absence of regional institutions (such as Bank of IGAD) worsen the situation, emerging and subsequent security threats such as terrorism, pastoral conflict, tense relationship among member states, undermining of the informal trade remains the road block of regional integration.